Surface to bulk Fermi arcs via Weyl nodes as topological defects - Kun Woo Kim (Nature Portfolio, 2016)
Understanding how surface Fermi arcs connect different Weyl nodes in presence of multiple Weyl-node pairs is intriguing yet unclear. Here, Kimet al. show that the winding of the Zak phase around each projected Weyl node manifests itself as a topological defect, leading to non-trivial surface as well as bulk Fermi arcs.